The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1088/0264-9381/23/4/l01
|View full text |Cite
|
Sign up to set email alerts
|

Quasinormal spectrum and quantization of charged black holes

Abstract: Black-hole quasinormal modes have been the subject of much recent attention, with the hope that these oscillation frequencies may shed some light on the elusive theory of quantum gravity. We study analytically the asymptotic quasinormal spectrum of a charged scalar field in the (charged) ReissnerNordström spacetime. We find an analytic expression for these black-hole resonances in terms of the black-hole physical parameters: its Bekenstein-Hawking temperature TBH , and its electric potential Φ. We discuss the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 28 publications
3
71
0
Order By: Relevance
“…for the static charged massive scalar field into the characteristic Klein-Gordon wave equation [50][51][52][53][54][55][56][57] …”
Section: Description Of the Systemmentioning
confidence: 99%
“…for the static charged massive scalar field into the characteristic Klein-Gordon wave equation [50][51][52][53][54][55][56][57] …”
Section: Description Of the Systemmentioning
confidence: 99%
“…For the area spectrum of a charged black hole, there have been many investigations. In terms of the reduced phase-space quantization, Barvinsky et al [19] found that the horizon area should be A n,p = 4π(2n + p + 1)l 2 p , where n, p = 0, 1, 2, · · · and the quantum number p corresponds to Q = ± √h p. Making use of Bohr's correspondence principle, Hod showed that the area spectrum was ∆ A = 4 ln 2l 2 p and ∆ A = 4 ln 3l 2 p respectively, for the event horizon area and the total areas of the inner horizon and outer horizon [20,21]. Recently, Banerjee et al [22] got the value ∆ A = 4l 2 p from the viewpoint of the tunneling paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that a Schwarzschild black hole is characterized by a discrete spectrum of gravitational resonances [8][9][10] with the fundamental asymptotic frequency [7,11] …”
mentioning
confidence: 99%